Dilemmas in the Management of Acute TBI: A Prospective Observational Study of Anterior Pituitary Dysfunction and Its Correlation with Outcome - Choudhary, Ajay; Sobti, Shivender; Dev, Nirankar; Kulshreshtha, Bindu; Sharma, Rajesh; Kaushik, Kaviraj; Kumar, Ashok (Indian Journal of Neurotrauma, 2023)
Background The frequency and pattern of endocrinal abnormalities among patients with traumatic brain injury occur more frequently than previously suspected.Objective The aim of this study was to assess anterior pituitary dysfunction in patients with moderate-to-severe traumatic brain injury and outcome after treatment.Materials and Methods One hundred patients with moderate-to-severe head injury presenting within 48 hours of injury were enrolled. Blood samples of all patients were taken for the hormonal assay at second day, at 2 weeks, 1 month, 3 months, and 6 months. Patients were evaluated by Glasgow coma scale (GCS), Glasgow outcome score (GOS), and hormone profile.Results The median GCS score was 10/15. Forty-four patients were operated and 56 patients were managed medically. Seven operated patients expired; 30 patients had good recovery. In conservative group, 46 patients had good outcome and two patients died. Cortisol and thyroid hormone values were changed prominently, followed by prolactin and growth hormone. On univariate analysis, association of GOS with fT3, fT4, serum prolactin, and serum cortisol was seen. On multivariate analysis, strong correlation of GOS with f T4 values was seen (p = 0.008)Conclusion Most of the hormonal deficiency occurs in immediate phase. Hormonal screening should be done to improve long term outcome.
Keywords: traumatic brain injury; anterior pituitary dysfunction; Glasgow coma scale; Glasgow outcome score; hormone